Comparison of Perceived Achievement of Complex Thinking Competency Among American, European, and Asian University Students - José Carlos Vázquez-Parra; Jenny Paola Lis-Gutiérrez; Linda Carolina Henao-Rodriguez; Carlos Enrique George-Reyes; Claudia Lorena Tramon-Pregnan; Susana Del Río-Urenda; Ma Esther B. Chio; Rasikh Tariq (Social Sciences)
Despite the growing focus of educational institutions on students’ practical abilities beyond theoretical knowledge, the perception that students have of their competencies is crucial for their effective application in professional contexts. Accordingly, this paper reports a study of 435 university students attending ten universities in eight countries in the Americas (Chile, Colombia, Mexico), Asia (Pakistan and the Philippines), and Europe (Spain, Finland, and Serbia). The goal was to measure their perceptions of their achievement of complex thinking competency and its sub-competencies. The intention was to identify how cultural, educational, and socioeconomic differences among countries account for the variances in the students’ self-assessment of competencies, impacting their professional preparedness. The study focused on the competency of complex thinking, considering its critical importance in solving current environmental problems. The analysis employed the non-parametric Brown–Forsythe statistical test and Bonferroni correction, given the non-normality and heteroscedasticity of the data. It was found that (i) there is no statistically significant difference by gender; (ii) there are statistically significant differences in all types of thinking per country, geographical area (continent), and Human Development Index (HDI).